ANALYSIS ON FATWA OF MAJELIS PERMUSYAWARATAN ULAMA ACEH (MPU) ON AGAINST PROHIBITION OF PUBG: A LEGAL VIEW BASED ON MASLAHAH AND MAFSADAH - Hudzaifah Achmad; Iqbal Syafri; Noor Naemah binti Abdul Rahman (Islam Futura, 2020)
Fatwa has the most important role to play in the development of society from time to time, and without exception Indonesia as a nation with the largest Muslim majority which requires the role of fatwa surely in order to dealt with or adapt to new issues. For instance, the recent fatwa issued by the Ulama Consultative Assembly (MPU) of Aceh on the prohibition of PUBG caused by an incident of terrorist attacks to the Muslim community in New Zealand. Therefore, the aims of this study is to analyse the fatwa issued by Ulama Consultative Assembly (MPU) of Aceg regarding the status haram of the PUBG based on the findins of Islamic principles, maslahah dan mafsadah. Particularly, the objectives of this research are as follows: 1). To explain the factors behind the Ulama Consultative Assembly (MPU) of Aceh in issuing a forbidden fatwa for the PUBG. 2). To describe the arguments or judgments that became the foundation of Ulama Consultative Assembly (MPU) of Aceh regarding their fatwa. 3). To analyse the haram fatwa against PUBG issued by Ulama Consultative Assembly (MPU) of Aceh through the concept of masalah and mafsadah.